2017
DOI: 10.15420/aer.2017.38/1
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Single-Procedure Success Rate of Pulmonary Vein Isolation

Abstract: To improve the single-procedural success and long-term outcomes of catheter ablation techniques for AF, there is a need for durable, contiguous and transmural lesions encircling the pulmonary veins (PV). Measurement of contact force (CF) between the catheter tip and the target tissue can optimise ablation procedures. A new approach to obtain single-procedure durable PV isolation (PVI) using the latest CF technology combined with the CARTO VISITAG ™ Module with Ablation Index (Biosense Webster) has been shown i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…The effectiveness of a first AF ablation according to Russian data was 66% when followed for one year after the intervention [12], which is comparable with global data [25]. However, due to the improvement of ablation technologies and the increase in the experience of the intervention, the efficacy of ablation continues to grow [26,27]. One of the tasks of the survey was to assess the expected effectiveness of AF ablation by operators themselves.…”
Section: Respondents' Perception Of the Current Af Ablation Effectivenessmentioning
confidence: 66%
“…The effectiveness of a first AF ablation according to Russian data was 66% when followed for one year after the intervention [12], which is comparable with global data [25]. However, due to the improvement of ablation technologies and the increase in the experience of the intervention, the efficacy of ablation continues to grow [26,27]. One of the tasks of the survey was to assess the expected effectiveness of AF ablation by operators themselves.…”
Section: Respondents' Perception Of the Current Af Ablation Effectivenessmentioning
confidence: 66%
“…Phlips et al 12 also applied the CLOSE protocol in 50 consecutive patients with paroxysmal AF and showed that, at 12 months, the rate of single‐procedure freedom from atrial tachyarrhythmia was 94%. Several other ongoing studies, including a multicenter trial, are evaluating the efficiency, safety, and efficacy of the CLOSE protocol 13,14 . A recent study, however, suggested that an AI value of 330 for the posterior and 450 for the anterior wall were as safe and reliable as higher values (380 for the posterior and 500 for the anterior wall) 15 …”
Section: Discussionmentioning
confidence: 99%
“…ВЕСТНИК АРИТМОЛОГИИ, № 3 (101), 2020 личения опыта проведения вмешательства, эффективность аблации продолжает расти [26,27]. Одной из задач опроса была оценка предполагаемой эффективности катетерного лечения ФП самими операторами.…”
Section: рис 6 доля пациентов с непароксизмальной фп которым провоunclassified